Kalanchoe olivierae (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae), a new species from southeastern South Africa - Smith, Gideon F.; Crouch, Neil R. (Phytotaxa, 2025)
A new species of Kalanchoe (Crassulaceae [subfam. Cotyledonoideae] tr. Kalanchoeae; K. subg. Kalanchoe), namely Kalanchoe olivierae, is described from eastern South Africa. Kalanchoe olivierae differs from K. rotundifolia, under which name material of the new species has thus far been placed, in vegetative and reproductive characters, with, inter alia vegetatively, its leaves being considerably bigger, elliptic-ovate to somewhat spathulate in outline, and basally distinctly guttered. Plants of the new species are often unbranched and can reach a height of over 1 m when in flower, while K. rotundifolia is a low-growing, often branched shrublet. The flowers of K. olivierae are larger than those of K. rotundifolia, and usually a pinkish orange colour, rather than uniformly dull red to orange. Kalanchoe olivierae is also contrasted with K. steyniae, which is a low-growing shrublet with bright crimson flowers. All three species are illustrated.